MATERNAL PREGNANCY OUTCOMES IN WOMEN WITH CARDIOMYOPATHY: A SYSTEMATIC REVIEW - Hilman, Feisal; Subhakti, M Alvian; Prabowo, Rafik (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Pregnancy poses significant cardiovascular challenges, affecting 1 to 4 of pregnancies due to maternal heart disease. Cardiomyopathies, leading indirect causes of maternal mortality globally, raise concerns during pregnancy, despite limited data on their impact and the accuracy of predictive scores like Carpreg and Zahara.  Maternal heart disease, comprising hypertensive disorders and cardiomyopathies, presents substantial risks during pregnancies, driving increased maternal mortality rates. The evolving landscape, marked by improved survival in congenital heart disease and delayed pregnancies with associated comorbidities, necessitates a more nuanced understanding and comprehensive predictive models for tailored care during pregnancy. Methods: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: Our search produced 15  results. After looking at the titles and summaries, we found 11  papers that fit our criteria. At first, we excluded several articles because they were written in review and case report style. But after reading the full papers carefully, we included five papers in our final analysis. These papers included prospective and retrospective studies. Conclusion: The investigation of pregnant women in Canadian obstetric centers unveiled that cardiac issues affect 16 of pregnancies, primarily with arrhythmias and heart failure, even in lower-risk cases, with complications emerging before birth. The study's precision in evaluating pregnancy-related cardiac risks, leading to a new CARPREG II risk index and emphasizing tailored surveillance and timely referrals, was notable. The ROPAC registry highlighted higher maternal mortality rates, stressing vigilant management throughout pregnancy and after delivery, emphasizing the necessity for specialized care and research advancements in this field.